Detection and Initial Characterization of Novel Capsular Polysaccharide among Diverse Campylobacter jejuni Strains Using Alcian Blue Dye - Karlyshev, Andrey V. (American Society for Microbiology, 2001)
We have recently demonstrated that most strains of Campylobacter jejuni produce capsular polysaccharide (CPS), which can be detected by immunoblotting with homologous Penner antisera on polyvinylidene difluoride membranes (A. V. Karlyshev, D. Linton, N. A. Gregson, A. J. Lastovica, and B. W. Wren, Mol. Microbiol. 35:529–541, 2000). In this report, we describe a universal and rapid staining procedure using Alcian blue for C. jejuni CPS, which does not rely on the availability of antisera and identifies CPS in untypeable strains. Furthermore, Alcian blue staining identified CPS in its lipid-free form directly on Tricine gels, and we demonstrate that CPS is thermostable and is accumulated in the culture supernatant in a lipid-free form. The identification of a newly described CPS and its lipid-free form in C. jejuni should prove invaluable in studying the pathogenesis and epidemiology of this important pathogen.